Resection of Ureteral Orifice During Transurethral Resection of Bladder Tumor: Functional and Oncologic Implications - Mano, Roy; Shoshany, Ohad; Baniel, Jack; Yossepowitch, Ofer (The Journal of urology, 2012)
Purpose We assessed the risk of upper urinary tract obstruction and tumor recurrence following ureteral orifice resection during transurethral resection of bladder tumor. Materials and Methods We reviewed the medical records of patients treated with transurethral resection of bladder tumors involving the ureteral orifice from 2008 to 2011. Patients with preoperative hydronephrosis or prior ipsilateral nephrectomy and those in whom a ureteral stent was placed during the procedure were excluded from analysis. Study end points were clinical or radiographic evidence of upper urinary tract obstruction and disease recurrence. Results The study group included 65 men (82%) and 14 women (18%) in whom a total of 84 orifice resections were performed. Hydronephrosis was observed in 11 patients (13%) during a median followup of 15 months (IQR 7–26). Hydronephrosis was secondary to muscle invasive disease in 5 patients (6%) and it resolved spontaneously in 3 (4%). In the remaining 3 patients (4%) overt stricture was detected at the ureterovesical junction, requiring endoscopic intervention. One patient was diagnosed with recurrent tumor in the upper urinary tract. The estimated bladder disease recurrence rate was 28% at 1 year and 54% at 2 years. Corresponding disease progression rates were 4% and 12%, respectively. Conclusions Ureteral orifice resection during transurethral resection of bladder tumor is rarely associated with detrimental renal obstruction or an increased risk of tumor recurrence in the upper urinary tract. New onset hydronephrosis is mostly attributable to muscle invasive disease or temporary obstruction. However, the few cases of overt stricture underscore the importance of meticulous followup with imaging.